LABEL TIME-TEMPERATURE INDICATOR MENGGUNAKAN CAMPURAN MINYAK NABATI UNTUK MEMONITOR MUTU MIKROBIOLOGI SUSU PASTEURISASI - Anis Khairunnisa; Nugraha Edhi Suyatma; Dede Robiatul Adawiyah (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2018)
Pasteurized milk (PM) is a perishable product requiring storage at cold temperatures to maintain its shelf life. However, the temperature fluctuations during transportation, handling, and storage could affect the number of microbial counts of the product. A time-temperature indicator (TTI) can be used to monitor product conditions in real time, so consumers know the condition of the product during transportation and storage. This study aims to determine the ability of a mixed vegetable oil (VOB) as a TTI indicator and evaluate the validity of TTI as an indicator of PM microbiological degradation. The VOB was produced from a mixture of palm oil (PO), canola oil (CA), and olive oil (OV) at ratios of 50:40:10 (C1), 50:25:25 (C2), and 50:10:40% (v/v) (C3), with the addition of 0.25% (m/v) of red dye (CI 16255). The VOBs were tested its for diffusion length, diffusion kinetics, and the accuracy of the prediction model of each indicator at isothermal temperatures. The VOB indicator can be applied to monitor the total growth of microbes in PM. The value of the activation energy (Ea) of each indicator was 34.289 (C1); 35,294 (C2) and 40,646 kJ/mol (C3), while the Ea value of the microbial spoilage in PM was 58,105 kJ/mol. The difference between the Ea PM value and each indicator was less than 25 kJ/mol. Indicating that the accuracy of the prediction model was good. At storage temperature of 29°C, the critical limit for PM spoilage occurs after 24 hours of storage which correlated with the diffusion length indicator of 6.50 (C1), 6.25 (C2), and 5.5 cm (C3). Overall, the indicators observed can be used to monitor the microbiological spoilage of PM, so that the actual quality of PM before consumption can be estimated.